ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KELULUSAN UJI KOMPETENSI NERS INDONESIA - Abdillah, Alvin (Universitas 17 Agustus 1945 Surabaya, 2016)
This competence test is same as national examination UN that we have done when we are in senior high school. The implementation of competence test was felt as accruing load especially for nurse profession student, itâ€™s because in previous time there was not competence test. In this case, â€œMajelis Tenaga Kesehatan Indonesiaâ€ (MTKI) decided that new graduation must have competence test. The implementation of competence test becomes a notice because nurse profession students who failed in this test they will unregister as a candidate of nurse in Indonesia, so that, the obligation must have competence test for nursing students caused some phenomena like afraid, strained, worried and downtrodden. The Research method that the researcher used was correlational quantitative and cross-sectional approach as the observationâ€™s method, variable try out, IPK, learning style and Indonesian nursing competency test passing grade. The population in this research was 145 students and the sample chosen 59 students. This research used random sampling technique. The instrument to collect data were documentation and questioner, analyze data used Fisherâ€™s Exact Test with 0,05.Â The result of the study showed that p=0.000 because p<a so that Ho is rejected, Thus it can be concluded that there are correlations between try out, IPK, learning style and Indonesian nursing competency test passing grade. For further researchers, I hope that can do continued study about other factors that influence Indonesian nursing competency test passing grade, so that next researcher can find the right solution to solve high value of failed problems in Indonesian nursing competency test passing grade.Keywords: Try Out, IPK, Learning Style and Indonesian Nursing Competency Test Passing Grade.